Effects of general anaesthesia and ultrasonography‐guided interscalene block on pain and oxidative stress in shoulder arthroscopy: A randomised trial. Issue 12 (12th October 2021) - Oksuz, Murat; Abitagaoglu, Suheyla; Kaciroglu, Ahmet; Koksal, Ceren; Ozturk, Burak Yagmur; Erel, Ozcan; Senat, Almila; Erdogan Ari, Dilek
Abstract: Background/aim: The aim of this study was to evaluate the effects of general anaesthesia and ultrasonography‐guided interscalene block on pain and oxidative stress evaluated by thiol‐disulphide balance and C‐reactive protein levels in patients undergoing shoulder arthroscopy. Materials and methods: A total of 42 patients aged 18‐75 years who were scheduled to undergo shoulder arthroscopy were randomised into interscalene block group (Group‐IB, n = 20) and general anaesthesia group (Group‐GA, n = 22). All patients received patient‐controlled analgesia during the postoperative period. Additional analgesics were administered to patients with a visual analogue scale score of >4. Native‐thiol, total‐thiol, disulphide and C‐reactive protein levels were measured. Patients' visual analogue scale scores, morphine and additional analgesic consumption were recorded. A shift in thiol‐disulphide balance towards decreased thiol and increased disulphide levels was regarded as an indicator of oxidative stress. Results: Pain level, morphine and additional analgesic consumption were higher in Group‐GA. Native‐thiol and total‐thiol levels were higher in Group‐IB postoperatively and also disulphide levels were lower at postoperative 18 hours. C‐reactive protein levels were similar in both the groups. Conclusion: Interscalene block induced less oxidative stress during the postoperative period, as evaluated by thiol‐disulphide balance. In shoulder arthroscopy, interscalene block provides more stable haemodynamics perioperatively and facilitates better postoperative pain control.